SAT0549 A SEMI-QUANTITATIVE MRI SCORING SYSTEM FOR INFLAMMATION IN JOINTS AND ENTHESES IN THE LOWER EXTREMITIES DEMONSTRATES GOOD RELIABILITY AND VALIDITY: POST-HOC ANALYSIS OF DATA FROM THE CRESPA TRIAL. (13th June 2020) - Krabbe, S.; Renson, T.; Jans, L.; Elewaut, D.; Van den Bosch, F.; Carron, P.; Ǿstergaard, M.
Abstract : Background: MRI allows an objective assessment of signs of inflammation in peripheral joints and entheses and is therefore of potential interest as outcome measure in trials. No knowledge exists on the reliability and validity of semi-quantitative MRI scores in the setting of peripheral spondyloarthritis (pSpA). Objectives: To describe the reliability of a semi-quantitative lower-extremity MRI scoring system, to investigate correlation with known measures of disease activity and ability to capture patients with improvement during treatment. Methods: In a post-hoc analysis, scores from 3 readers (LJ, MØ, SK) who independently assessed MRI images of pelvis (except sacroiliac joints), knees and ankles in the CRESPA trial blinded to chronology and all clinical data, were further analyzed. Entheses were scored 0-3 (none/mild/moderate/severe) for soft tissue inflammation (19 sites) and 0-3 for bone marrow edema (24 sites), joints were scored 0-3 for effusion/synovitis (10 sites) and 0-3 for bone marrow edema (22 sites). MRI score was defined as the sum of scores from all joints and entheses (i.e. all 75 sites). The CRESPA trial (NCT01426815 ) included 60 patients with early pSpA, defined as a symptom duration of <12 weeks. All patients fulfilled the Assessment of SpondyloArthritis international Society criteria for pSpA; data from 56 patients with available MRI images at baseline were included in this analysis, 46 had available MRI images at follow-up. Follow-up MRI was only performed if sustained clinical remission was reached. Reliability was assessed using two-way intra-class correlation coefficient (ICC) models by absolute agreement, single-measure (relevant when using scores from 1 reader) and average-measure (relevant when using averaged scores from 3 readers). Results: MRI scores at baseline were mean 7.2 (median 5, inter-quartile range 3 to 9, range 0 to 32). MRI change scores were mean −3.1 and (median −1, IQR −4 to 0, range −18 to 2). MRI status scores at baseline (n=56) had single measure ICC 0.78 (95% CI: 0.66-0.87) and average measure ICC 0.92 (0.85-0.95). MRI change scores (n=46) had single measure ICC 0.73 (0.57-0.84) average measure ICC 0.89 (0.80-0.94). MRI status scores correlated significantly with CRP, ESR, swollen joint count and pain score. Patients with PSpARC40 response (n=34) (≥40% improvement in disease activity according to the Peripheral SpA Response Criteria) had larger decreases in MRI scores compared to patients without PSpARC40 response (n=11), mean −3.4 vs. −1.0, p=0.03. When using all MRI data from pelvis, knees and ankles combined, more patients could be identified to have improvement, as compared to only taking one of three parts into account. Conclusion: The semi-quantitative lower-extremity MRI score showed acceptable reliability and validity. The ability to capture response was best when combining information from all available areas that were imaged, i.e. both pelvis, knees and ankles. *First authorship is shared between SK and TR. Disclosure of Interests: Simon Krabbe Grant/research support from: AbbVie, MSD, Novartis, Thomas Renson: None declared, Lennart Jans: None declared, Dirk Elewaut: None declared, Filip van den Bosch Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Speakers bureau: AbbVie, Celgene Corporation, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Philippe Carron: None declared, Mikkel Ǿstergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Celgene, Merck, and Novartis, Consultant of: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Hospira, Janssen, Merck, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Roche, Sandoz, Sanofi, and UCB